History of ABVD alters the number of oocytes vitrified after in vitro maturation in fertility preservation candidates. (July 2016) - Sonigo, Charlotte; Seroka, Alice; Cédrin-Durnerin, Isabelle; Sermondade, Nathalie; Sifer, Christophe; Grynberg, Michael
Aim: This retrospective case–control study aimed at analyzing the results of in vitro maturation (IVM) of oocytes, used for fertility preservation (FP), in patients with history of ABVD (adriamycin, bleomycin, vinblastine and dacarbazine) for classical Hodgkin lymphoma.Patients & methods: A total of 22 candidates for FP, having received ABVD at least 2 years before IVM for FP were studied. IVM results were compared with those of 44 breast cancer patients, without history of chemotherapy, matched for ovarian reserve parameters.Results: The number of cumulo-oocyte complexes recovered and the total number of matured oocytes vitrified was lower in patients having received AVBD (5.5 ± 4.8 vs 8.5 ± 4.4 oocytes; p = 0.03 and 3.5 ± 3.7 vs 6 ± 3.0 oocytes; p < 0.04, respectively).Conclusion: In light of these results, FP should be discussed before ABVD.